O papel indutor do PIBID na formação de professores reflexivos 2014-2016 - Silva, Lais Fernanda da (2020)
This dissertation is linked to the Education of Teachers and Other Educational Agents research group of the Post-Graduate Program in Education - Master and Doctorate - from the Federal University of São Carlos (UFSCar). The general objective of the research was to analyze the contributions and limits of Pibid in the formation of reflective teachers, pibidians of Pedagogy between 2014 and 2016, years with the largest grant of scholarships from different Higher Education Institutions in Brazil. The specific objectives sought to identify, from the perspective of the graduates, the contributions and limits of Pibid in teacher education, to understand whether Pibid has been configured in a space for reflection on teaching practice and how it is done, in addition to analyzing which aspects / elements of Pibid can be configured in tools that enhance participants' learning and how they can promote the development of a willingness for reflection, following a qualitative approach of the descriptive-interpretative type. Data collection was performed through the application of a questionnaire and five interviews with a semi-structured script, in order to find out who the Brazilian pibidians are and whether Pibid was a space for reflective training. The results show that Pibid is an important program for initial teacher education and that through professional insertion, as well as through different training practices, it provided several contributions in initial teacher education such as: the possibility of articulation between theory and practice; maintaining the student's permanence in graduation; the possibility of dedicating oneself only to studies; participation in scientific events; promoting the reduction of the “reality shock”; the possibility of learning from living in the school routine and the reframing of the profession. The limits listed by the pibidians, however, were the low value of the scholarship, the distance between the program coordinator and supervisor, the low scope of Pibid and the few moments of reflection. Despite the limits, all Pedagogy pibidians (2014-2016), considered Pibid as a fundamental element in their education, and many showed that Pibid was a program that provided moments of reflection on their practices, so we consider that Pibid collaborates grandly for the formation of reflective teachers in Brazil.